A spatial and cellular distribution of rabies virus infection in the mouse brain revealed by fMOST and single‐cell RNA sequencing. Issue 1 (20th January 2022) - Zhang, Yachun; Xing, Xudong; Long, Ben; Cao, Yandi; Hu, Simeng; Li, Xiangning; Yu, Yalan; Tian, Dayong; Sui, Baokun; Luo, Zhaochen; Liu, Wei; Lv, Lei; et al.
Abstract: Background: Neurotropic virus infection can cause serious damage to the central nervous system (CNS) in both humans and animals. The complexity of the CNS poses unique challenges to investigate the infection of these viruses in the brain using traditional techniques. Methods: In this study, we explore the use of fluorescence micro‐optical sectioning tomography (fMOST) and single‐cell RNA sequencing (scRNA‐seq) to map the spatial and cellular distribution of a representative neurotropic virus, rabies virus (RABV), in the whole brain. Mice were inoculated with a lethal dose of a recombinant RABV encoding enhanced green fluorescent protein (EGFP) under different infection routes, and a three‐dimensional (3D) view of RABV distribution in the whole mouse brain was obtained using fMOST. Meanwhile, we pinpointed the cellular distribution of RABV by utilizing scRNA‐seq. Results: Our fMOST data provided the 3D view of a neurotropic virus in the whole mouse brain, which indicated that the spatial distribution of RABV in the brain was influenced by the infection route. Interestingly, we provided evidence that RABV could infect multiple nuclei related to fear independent of different infection routes. More surprisingly, our scRNA‐seq data revealed that besides neurons RABV could infect macrophages and the infiltrating macrophages played at least three different antiviral roles during RABV infection. Conclusion: This study draws a comprehensively spatial and cellular map of typical neurotropic virus infection in the mouse brain, providing a novel and insightful strategy to investigate the pathogenesis of RABV and other neurotropic viruses. Abstract : The three‐dimensional distribution of rabies virus (RABV) is revealed by fMOST techniques. The spatial distribution of RABV in the mouse brain depends on the infection route. Three different antiviral roles of macrophages are identified during RABV infection. Apoptotic NK cells in RABV‐infected brains have been observed.